Technology and Innovation in Insurance– Present and Future Technology in Indian Insurance Industry - Dr. P.Revathi (International Journal of Engineering and Management Research, 2020)
Insurance companies are unique — most of their interactions with customers happen through an agent. In effect, a chunk of technology investment goes into improving agent experience. Insurers have developed systems to advise agents on products tailored for specific customers, depending on their history with the insurer and income band. Bajaj Allianz Life Insurance has a mobile app to hire agents. This helps in training, exams and licensing. It has brought on board 15,700 consultants digitally in the past year, cutting down processing time by half. Insurers have launched mobile phone apps, making it easier for customers to transact with them. They are, slowly and surely, moving towards paperless claims as well. These are, however, only the first steps in digital transformation. Changing core systems is expensive and complicated. So, most transformation initiatives focus on improving systems of engagement with customers. With the constant advancements and better use of digital tools in the last few years; most of these challenges seem to be addressed efficiently. While technologies such as Robotic Process Automation (RPA), Artificial Intelligence (AI), Block chain, and Advanced Analytics are working as promoters to enhance the importance of insurance, the insurers are working hard to create a more streamlined and integrated insurance system.